The chess game in the school context for students with visual impairment: a systematic review (Research, Society and Development, 2022)
The present research, from a qualitative perspective, aimed to investigate the productions on chess related to the student with Visual Impairment (DV) in the school context, from research and studies already published, seeking to present reflections and discoveries that contribute to the practice of the game in the educational field. And in this sense, the study also helps in understanding the development of productions and publications in the investigated field. A literature review was carried out (Figueiredo, 1990) to identify what had already been published on the subject related to the educational field. The search was carried out through a virtual environment and delimited to the CAPES Periodicals Portal on January 9, 2022, using the keywords Chess and visual impairment. Eight works were found and after reading only three were analyzed because they relate to the investigated themes. After the analysis, we understand that the works contribute to show how the practice of Chess can be beneficial to students with VI in the school context, contributing to their development and the construction of knowledge in different areas. It is hoped that the contributions presented in the text can resonate in other pedagogical practices contributing to ethical, dignified and inclusive education.